Study Interest of Senior and Vocational High School Graduates in the Family Welfare Education Program - Ilyasa Afriantoro; Elida Elida; Wiwik Gusnita; Juliana Siregar (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2025)
This study aims to identify the differences in learning interest between students who graduated from general senior high schools (SMA) and vocational high schools (SMK) in compulsory foundational courses within the Family Welfare Education Study Program. It also aims to describe the level of learning interest within each group. This research employs a descriptive-comparative approach. The population consists of active students in the Family Welfare Education Study Program who graduated from SMA, SMK specializing in Culinary Arts (Boga), and SMK specializing in Fashion (Busana), with a total sample of 80 respondents. Data were collected using a Likert-scale questionnaire and analyzed using descriptive hypothesis testing and a t-test, which was preceded by non-parametric statistical testing to determine whether there was a significant difference in scores between groups within the same sample. The results showed that SMA graduates had an average learning interest score of 147.65 (categorized as moderate), SMK Boga graduates had an average of 145.20 (categorized as low to moderate), and SMK Busana graduates had an average of 146.95 (categorized as moderate). The ttest results showed a t-value = 0.831 < t-table = 1.66 and a Sig. (2-tailed) = 0.409 > 0.05, indicating that there is no significant difference in learning interest between SMA and SMK graduates in the compulsory foundational courses of the study program. These findings suggest that educational background does not significantly influence students' interest in learning during lectures. This research provides important insights into how prior educational background affects student interest in core courses and may serve as a valuable reference for curriculum developers in higher education institutions.